TUGAS POKOK DAN FUNGSI APOTEKER SEBAGAI PELAKSANA PENGADAAN PERBEKALAN FARMASI DI RUMAH SAKIT - Limba, Kristina Megi (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 11 No 1 (2021): Indonesian Journal of Legal and Forensic Sciences, 2021)
One of the pharmaceutical services in the Hospital Pharmacy Installation is the management of pharmaceutical supplies. At the management stage, the procurement of pharmaceutical supplies greatly affects the availability of drugs in hospitals. Procurement is an activity to realize the planning needs for pharmaceutical supplies. The process of procuring pharmaceutical supplies must ensure availability, quantity, correct time at affordable prices according to quality standards. A pharmacist is in charge of every pharmaceutical supplies activity in the hospital. Therefore an understanding is needed for pharmacists regarding the main duties and functions of pharmacists in the procurement system. This study aims to discuss the main duties and functions of pharmacists in drug management, particularly the procurement of pharmaceutical supplies in hospitals. The research method used is literature study related to the procurement of pharmaceutical supplies in hospitals. The main duties and functions of pharmacists in the pharmaceutical supplies process include selecting the required pharmaceutical supplies, determining suppliers, determining the procurement method to evaluating the procurement process in hospitals.